Most Influential Author In Indonesian Social Work Practice Research (Universitas Terbuka, 2024)
The ratification of Law number 14 of 2019 concerning Social Workers is proof of a major step in the historical development of social work practices in Indonesia. Along with the complexity of the social issues faced, a deep understanding of the development of social work practice research is very important. However, since the practice of social work grew from 1945 until five years after the passage of the law related to the profession of social work, there has not been a roadmap for conference research in the field of social work practice in Indonesia. This study seeks to analyze the development of research in the field of social work practice in Indonesia in the last ten years and analyze the strengths and weaknesses of the field of social work practice in Indonesia. It is hoped that the results of this study will be able to provide an overview of the dynamics of the research, so it is very important as a consideration for policy input in the development of social work/social welfare science curriculum, designing intervention programs, and identifying strengths and knowledge gaps so that social workers in Indonesia have competitiveness in the international arena. Several concepts will be used in this study, including the concept of social work practice and the concept of social welfare. The bibliometric method approach will be used in this study, by analyzing the numerical trend of the number of publications in the last 10 years, the quantitative distribution of publication years, the characteristics of authors, and the relevance of subtopics. The search for research articles will use Harzing's Publish or Perish and Google Scholar applications as data retrieval databases, then analyzed in depth including research productivity, regional distribution, the most influential researchers, mapping research themes, as well as analysis of research strengths and weaknesses in the field and visualized using VOSViewer and several other applications.